(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Melkumova T. W. Studying the adjectives on Ukrainian as foreign language lessons for the first-course students. The article deals with the set of tasks for actualization, intensification, systematization, generalization and consolidation of foreign students’ knowledge about grammar adjective categories and combination of adjectives and nouns. The methods of studying the meaning adjective categories and degrees of comparison of qualitative adjectives are given.